Empowering the Islamic Creative Economy through Traditional Weaving Enterprises: A Case Study of Community Welfare Development in Central Lombok, Indonesia - Bathin Bathin; Mashur Mashur (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study explores the empowerment strategies of the creative economy sector through traditional weaving enterprises in Pujut District, Central Lombok, Indonesia, from the perspective of Islamic economics. Using a qualitative descriptive approach, the research aims to analyze how weaving artisans, supported by local community networks and religious values, contribute to improving household welfare. Data were collected through interviews, observation, and documentation involving community leaders, weaving artisans, and cooperative members. The findings reveal that empowerment occurs through capacity building, mutual cooperation, and digital marketing adaptation. Islamic ethical principles such as amanah (trustworthiness), ta’awun (mutual help), and halal livelihood guide artisans’ behavior and production processes. Despite facing challenges such as limited capital, raw material scarcity, and low technological literacy, the weaving community exhibits strong resilience grounded in faith-based motivation and social solidarity. The study concludes that the integration of Islamic moral economy and creative entrepreneurship fosters inclusive, sustainable welfare for rural communities. This research contributes to the discourse on Islamic creative economy development and highlights the role of traditional crafts as vehicles for spiritual and economic empowerment.